Changing pattern of prescribing antidiabetic agents in patients suffering from diabetes mellitus - Chaudhari, Vipul P.; Ganguly, Barna (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug utilization studies are powerful exploratory tools to ascertain the role of drugs in society. They create a sound sociomedical and health economic basis for healthcare decision making. The study was aimed to find out the changing pattern of prescribing the antidiabetic agents in patients suffering from diabetes mellitus type 1 and 2. Methods: It was a cross sectional study done on 200 patients suffering from type 1 and 2diabetes. Indoor patients and diabetes mellitus due to secondary cause were excluded. Each patient was followed up over a period of 1 year and the analysis of the prescriptions was done during that period. At end of study only 129 patients could be included for analysis. Results: In this study the maximal change in medicine was with pioglitazone which was discontinued as a 1st change in 6.2% of patients followed by metformin [5.4%], insulin [4.6%], and glipizide [3.8%]. The drug most commonly added as a first change was glipizide [11.6%] followed by metformin [10.0%] and pioglitazone [7.7%]. In order of 2nd change the most common drug discontinued was insulin [4.6%] followed by pioglitazone [3.8%] whereas drug commonly added as second change was insulin [2.3%] followed by glipizide [1.5%] and pioglitazone [1.5%]. In our cross sectional study average onset of 1st change was found to be at 4.38±2.75 months for discontinuation of drug and 3.75±2.42 months in adding the drugs. Conclusions: Due to lack of certain records, it is envisaged that the change of medicine both discontinuation as well as addition was done because of blood glucose control, cost factor [in case of pioglitazone] as well as patient’s compliance.